Sosialisasi SADARI sebagai strategi efektif membangun ketahanan kesehatan reproduksi - Holida, Siti Solihat; Yusdian, Yudi (JOURNAL of Public Health Concerns, 2025)
Background: Pest control with pesticides effectively increases agricultural yields, but exposure to synthetic compounds such as organophosphates carries the risk of neurological damage, reproductive disorders, and carcinogenesis, including increased incidence of breast cancer. Students from the Faculty of Agriculture, Bale University, Bandung, are vulnerable to exposure during field practice, while their knowledge of early breast cancer detection remains low. The Breast Self-Examination (SADARI) education program is proposed as a low-cost and practical preventive measure to increase awareness and early detection skills. This initiative supports students' role as agents of change in strengthening the health of rural communities. Purpose: To increase knowledge and awareness among students from the Faculty of Agriculture, Bale University, Bandung, regarding reproductive health and SADARI as an early detection method for breast cancer. Method: The type of activity carried out was health education to the community with the theme "Socialization of BSE and Clinical Breast Examination: An Effective Strategy to Build Reproductive Health Resilience in Agricultural Students." The target of this activity was 23 third-semester students, who were of productive age and vulnerable to various reproductive health risks. The first activity was held on Saturday, March 23, 2024, from 08.00 WIB to 15.00 WIB. at the Faculty of Agriculture Experimental Garden, in the form of demonstrations and direct practice by participants, such as breast self-examination (BSE) simulations, which are an important part in developing participants' practical skills. The second activity was held on Monday, April 1, 2024, from 08.00 WIB to 15.00 WIB. in the classroom, participants were given educational materials regarding reproductive health, breast cancer risk factors, and steps to perform BSE correctly, which were delivered through presentations, educational videos, and interactive discussions to explore participants' understanding and provide a question and answer space. Results: The pre-test showed that 7 (30.4%) respondents' knowledge of early detection and breast cancer risk was in the good category, 12 (52.2%), and 4 (17.4%) were in the poor category. Meanwhile, the post-test respondents' knowledge of early detection and breast cancer risk was all in the good category, at 23 (100.0%). Conclusion: The community service activity themed Breast Self-Examination (SADARI) education and outreach for agricultural students was implemented smoothly and successfully increased participants' knowledge, awareness, and skills in maintaining reproductive health and conducting early breast cancer detection. Through a combination of theoretical counseling and direct practice, students gained conceptual understanding and practical experience as health education agents in the community, particularly in rural areas. Suggestion: It is hoped that this activity will be carried out continuously by participants, thereby encouraging independent SADARI practice and disseminating information and correct health practices in rural areas and the agricultural sector, which will be the participants' primary service areas, as a form of preventive behavior in maintaining reproductive health. Keywords: Breast cancer prevention; Pesticide exposure; Reproductive health; SADARI method Pendahuluan: Pengendalian hama dengan pestisida efektif meningkatkan hasil pertanian, namun paparan senyawa sintetik seperti organofosfat berisiko memicu kerusakan neurologis, gangguan reproduksi, dan karsinogenesis, termasuk meningkatnya insiden kanker payudara. Mahasiswa Fakultas Pertanian Universitas Bale Bandung rentan terpapar saat praktik lapangan, sementara pengetahuan deteksi dini kanker payudara di kalangan mereka masih rendah. Program edukasi mandiri SADARI (Pemeriksaan Payudara Sendiri) diusulkan sebagai langkah preventif murah dan praktis untuk meningkatkan kesadaran dan keterampilan deteksi dini. Inisiatif ini mendukung peran mahasiswa sebagai agen perubahan dalam memperkuat kesehatan masyarakat pedesaan. Tujuan: Meningkatkan pengetahuan dan kesadaran Mahasiswa fakultas pertanian Universitas Bale Bandung  tentang kesehatan reproduksi dan SADARI sebagai upaya deteksi dini terhadap kanker payudara. Metode: Jenis kegiatan yang dilaksanakan berupa pendidikan kesehatan kepada masyarakat dengan mengusung tema “Sosialisasi SADARI dan Pemeriksaan Klinis Payudara: Strategi Efektif Membangun Ketahanan Kesehatan Reproduksi Mahasiswa Pertanian.” Sasaran kegiatan ini adalah 23 mahasiswa semester III, yang berada pada usia produktif dan rentan terhadap berbagai risiko kesehatan reproduksi. Kegiatan pertama dilaksanakan pada hari sabtu tanggal 23 Maret 2024, mulai pukul 08.00 WIB hingga 15.00 WIB. di Kebun Percobaan Fakultas Pertanian, berupa demonstrasi dan praktik langsung oleh peserta, seperti simulasi pemeriksaan payudara sendiri (SADARI), yang menjadi bagian penting dalam membentuk keterampilan praktis peserta. Kegiatan kedua dilaksanakan pada hari senin tanggal 1 April 2024, pukul 08.00 WIB hingga 15.00 WIB. di ruang kelas, peserta diberikan materi edukatif mengenai kesehatan reproduksi, faktor risiko kanker payudara, serta langkah-langkah melakukan SADARI dengan benar, yang disampaikan melalui presentasi, video edukatif, dan diskusi interaktif untuk menggali pemahaman peserta serta memberikan ruang tanya jawab. Hasil: Menunjukkan bahwa tingkat pengetahuan responden tentang deteksi dini dan risiko kanker payudara pre-test dalam kategori baik sebanyak 7 (30.4%), kategori cukup sebanyak 12 (52.2%), dan kategori kurang sebanyak 4 (17.4%). Sedangkan tingkat pengetahuan responden tentang deteksi dini dan risiko kanker payudara post-test semuanya dalam kategori baik yaitu sebanyak 23 (100.0%). Simpulan: Kegiatan pengabdian masyarakat bertema edukasi dan sosialisasi SADARI (Pemeriksaan Payudara Sendiri) bagi mahasiswa pertanian telah terlaksana dengan lancar dan berhasil meningkatkan pengetahuan, kesadaran, dan keterampilan peserta dalam menjaga kesehatan reproduksi serta melakukan deteksi dini kanker payudara. Melalui kombinasi penyuluhan teori dan praktik langsung, mahasiswa memperoleh pemahaman konseptual sekaligus pengalaman aplikatif sebagai agen edukasi kesehatan di masyarakat, khususnya di wilayah pedesaan. Saran: Diharapkan kegiatan ini dilakukan secara berkelanjutan oleh peserta, sehingga dapat mendorong praktik SADARI secara mandiri dan menyebarluaskan informasi serta praktik kesehatan yang benar di lingkungan pedesaan dan sektor pertanian yang menjadi wilayah pengabdian utama peserta kelak, sebagai bentuk perilaku preventif dalam menjaga kesehatan reproduksi.